2021
DOI: 10.1111/jocs.15506
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of mitral valve repair over replacement in the elderly: a systematic review and meta‐analysis

Abstract: Objectives: Mitral valve (MV) repair has demonstrated excellent short-and longterm outcomes, however, its merit in the elderly population is still debated. We conducted a meta-analysis of studies that have compared the MV repair to replacement in the elderly population.Methods: A systematic literature search was conducted for any study published on MV surgery on elderly patients (≥75 years old). A pooled risk-ratio meta-analysis was done to evaluate short-term mortality, postoperative complications, surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…This meta‐analysis 1 shows that patients with rheumatic MR have, correctly, a high prevalence of MVR (87%) and nobody doubts that MVR is the best solution for this etiology, irrespective of the global concept of the superiority of repair on replacement. On the other side, we know that degenerative MR can be, in expert hands, repaired in many patients (65% in this study 1 ) with good long‐term freedom from residual MR. But in patients with ischemic MR repair failure can be high in the midterm 10 and the risk of a reoperation can be often less acceptable than in younger patients.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…This meta‐analysis 1 shows that patients with rheumatic MR have, correctly, a high prevalence of MVR (87%) and nobody doubts that MVR is the best solution for this etiology, irrespective of the global concept of the superiority of repair on replacement. On the other side, we know that degenerative MR can be, in expert hands, repaired in many patients (65% in this study 1 ) with good long‐term freedom from residual MR. But in patients with ischemic MR repair failure can be high in the midterm 10 and the risk of a reoperation can be often less acceptable than in younger patients.…”
mentioning
confidence: 86%
“…Even if repair can be performed in presence of some specific etiologies, as degenerative MR or secondary MR, there are always cases where a replacement can be an acceptable solution compared to a repair with uncertain future, regardless of our believes and our technical ability. This meta-analysis 1 shows that patients with rheumatic MR have, correctly, a high prevalence of MVR (87%) and nobody doubts that MVR is the best solution for this etiology, irrespective of the global concept of the superiority of repair on replacement. On the other side, we know that degenerative MR can be, in expert hands, repaired in many patients (65% in this study 1 ) with good long-term freedom from residual MR.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…6). Since mitral valve replacement is associated with poorer survival than mitral valve repair, [55][56][57] this finding is important for individual assessment by the heart valve team.…”
Section: Mitral Valvementioning
confidence: 99%
“…Surgical exploration showed scattered and small vegetations on the left ventricular surface of the anterior mitral valve without obvious valve leaf thickening, ulceration, or involvement of chordae tendineae, so mitral valve repair was performed. Several studies have shown that mitral valve repair has low mortality, fewer complications, and a better long-term prognosis than mitral valve replacement (24)(25)(26). Of these cases, only one death occurred in a 58-yearold man who refused surgery and died of multiple cerebral infarctions several days after admission, suggesting that timely treatment is of great importance in the acute phase of infection.…”
Section: Frontiers In Cardiovascular Medicinementioning
confidence: 99%